Clinical, Endoscopic, and Histopathological Features of HER2 Expression and Two-Year Survival in Gastric Adenocarcinoma - Deka Larasati; Marcellus Simadibrata; Nur Rahadiani; Ikhwan Rinaldi; Ruswhandi -; Edi Mulyana; Lianda Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Background: HER2 is a proto-oncogene and therapeutic target in advanced gastric adenocarcinoma. Reports on its association with clinicopathological features and prognosis remain inconsistent. This study aimed to evaluate the relationship of clinical, endoscopic, and histopathological features with HER2 expression and its impact on two-year survival.Methods: A retrospective cohort study was conducted among patients ≥18 years with newly diagnosed gastric adenocarcinoma at four hospitals in Jakarta (2015–2019). Eligible cases had complete records and paraffin blocks. HER2 was assessed by immunohistochemistry and CISH using ToGA criteria. Chi-square/Fisher’s tests evaluated associations, while survival was analysed with Kaplan-Meier and Cox regression. Results: Among 122 patients, 15 (12.3%) were HER2-positive. More frequent expression was observed in liver metastases than in non-liver metastases (17.6% vs. 10.2%), in Borrmann type I/II than in Borrmann type III/IV (16.1% vs. 9.1%), in moderately rather than in poorly differentiated tumors (14.3% vs. 11%), and in intestinal-type rather than in diffuse/mixed-type tumors (13.9% vs. 10%); however, none were statistically significant. Median survival was 5 months in HER2-positive patients and 4 months in HER2-negative patients. HER2 was not significantly associated with two-year survival (HR [95% CI] = 1.12 [0.61, 2.06]). Mortality in patients with palliative therapy was higher than that of those with definitive/therapeutic therapy (76.8% vs 75.8%; HR = 1.547 [1.022, 2.343]). The combination of resection and chemotherapy intervention provided a protective effect on mortality with HR = 0.456 [0.219, 0.95]. There was a significant association between resection-chemotherapy combination therapy and survival in subjects with negative HER2 expression (HR = 0.409 [0.176, 0.947]. Conclusion: In this study, HER2 expression in gastric adenocarcinoma was 12.3%. HER2 expression tended to be higher in liver metastases, Borrmann type I/II, moderate differentiation, and intestinal type histopathology results. Combination therapy with resection and chemotherapy had a protective effect on mortality in this study. Median survival in HER2-positive patients was higher than in HER2-negative patients, but HER2 expression status was not a prognostic factor for two-year survival in gastric adenocarcinoma